Modulation of Voltage-Gated Sodium Channels by Activation of Tumor Necrosis Factor Receptor-1 and Receptor-2 in Small DRG Neurons of Rats. (4th October 2015) - Leo, M.; Argalski, S.; Schäfers, M.; Hagenacker, T.
Abstract : Tumor necrosis factor- (TNF-) α is a proinflammatory cytokine involved in the development and maintenance of inflammatory and neuropathic pain. Its effects are mediated by two receptors, TNF receptor-1 (TNFR-1) and TNF receptor-2 (TNFR-2). These receptors play a crucial role in the sensitization of voltage-gated sodium channels (VGSCs), a key mechanism in the pathogenesis of chronic pain. Using the whole-cell patch-clamp technique, we examined the influence of TNFR-1 and TNFR-2 on VGSCs and TTX-resistant NaV1.8 channels in isolated rat dorsal root ganglion neurons by using selective TNFR agonists. The TNFR-1 agonist R32W (10 pg/mL) caused an increase in the VGSC current ( I Na(V) ) by 27.2 ± 5.1%, while the TNFR-2 agonist D145 (10 pg/mL) increased the current by 44.9 ± 2.6%. This effect was dose dependent. Treating isolated NaV1.8 with R32W (100 pg/mL) resulted in an increase in I NaV(1.8) by 18.9 ± 1.6%, while treatment with D145 (100 pg/mL) increased the current by 14.5 ± 3.7%. Based on the current-voltage relationship, 10 pg of R32W or D145 led to an increase in I Na(V) in a bell-shaped, voltage-dependent manner with a maximum effect at −30 mV. The effects of TNFR activation on VGSCs promote excitation in primary afferent neurons and this might explain the sensitization mechanisms associated with neuropathic and inflammatory pain.